"The Lunatics Are on the Loose...": European Fluxus festivals 1962-1977 - Stegmann, Petra; Van der Meijden, Peter; Rios, Henar Rivièra; Roms, Heike; Ugelstad, Caroline (Potsdam Down with Arts!, 2012)
Publication in English on the occasion of the exhibition The lunatics are on the loose & EUROPEAN FLUXUS FESTIVALS 1962-1977Extensive documentation of 32 selected European Fluxus events in Aachen, Aberystwyth, Amsterdam, Berlin, Budapest, Copenhagen, Düsseldorf, London, Madrid, Nizza, Oslo, Paris, Prague, Poznan, Rotterdam, Scheveningen, Stockholm, Vilnius, Wiesbaden, WuppertalContributions by Jennifer Burkard, Myriam Kroll, Peter van der Meijden, Susanne Rennert, Henar Rivière Ríos, Heike Roms, Vanja Sisek, Petra Stegmann, Caroline UgelstadArtistic contributions by Eric Andersen, Philip Corner, Alison Knowles, JarosBaw KozBowski, Larry Miller, Ann Noël, Ben Patterson, Tamas St.Turba Since 1962, a long series of European cities has witnessed Fluxus concerts. The loose formation of young artists that worked under the Fluxus banner became known for shaving their heads on stage, working with butter and eggs for a time, destroying a grand piano and shouting at the top of their voices. The audience and the media were shocked: The lunatics are on the loose!, a spectator scratched onto a poster advertising the Fluxus International Festival of Newest Music in Wiesbaden. Music With Eggs, They Hang Up Cabbage and Say It Is Art, New Music Asylum Style and Is There Nobody Who Can Stop These Happenings were some of the headlines.The aim of the Fluxus artists was to destroy the boundaries of art and the traditional artistic genres. They set out to overcome the bourgeois notion of art and rejected the classical material work of art. Their works were informed by an interest in the everyday and the musical aspects of sound and simple actions. They consisted first and foremost of short scores or instructions (event scores) that could be performed in countless different ways. Because of this different outlook, everyday actions could be understood as compositions on a par with classical works of art. Fluxus brought about a huge extension of the musical and artistic spectrum.The exhibition represents a first step towards a comparative study of the European Fluxus events and their history. In the installation, numerous evens, both large- scale and small, that took place in Aachen, Aberystwyth, Amsterdam, Berlin, Budapest, Düsseldorf, Copenhagen, London, Madrid, Nice, Oslo, Paris, PoznaD, Prague, Rotterdam, Scheveningen, Stockholm, Vilnius, Wiesbaden and Wuppertal are documented by means of scores and photographs. Background information is provided in the shape of a database that is accessible via iPads. Scantily documented events receive as much attention as well-documented ones. We hope that some of the lacunas will be filled during the course of the exhibition tour. Eyewitnesses are warmly invited to share their memories with us. Visitors are welcome to perform Fluxus compositions in the exhibition space and up throught the towers of Nikolaj where you can find Fluxus scores!
Keywords: 20th Century (1901-2000); Avant-garde; Performance art; Europe